Estrategia industrial de Chile para la década de los años 70 Documentos Inéditos 1969-1970 - Bitar, Sergio (Ariadna Ediciones, 2022)
Between 1968 and 1970 CORFO prepared one of the most complete industrial strategy proposals for Chile 1970-80. This program was not implemented and the texts remained undisclosed. The present work of historical recovery transports us to the beginning of the 70s, convulsive times that marked a turn in the country's economy and in the work of CORFO, first with the government of Salvador Allende and, later, with the dictatorship. Today, when the country embraces the idea of ​​giving a new impetus to Chile's industrial development, it is that we must put into perspective what was done then, and on that basis imagine a new stage with ambition. As CORFO's Executive Vice President, José Miguel Benavente, expressed it in 2022, "we want to move towards a new development model that is more inclusive and sustainable, territorially equitable and based no longer on the simple extraction and export of natural resources, but on more intensive in science, technology and innovation"